2010
DOI: 10.1002/btpr.433
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of an antitumor‐analgesic peptide from the venom of Mesobuthus martensii Karsch by small ubiquitin–related modifier fusion in Escherichia coli

Abstract: To prevent protein aggregation, some proteins are usually expressed as fusion proteins from which target proteins can be released by proteolytic or chemical reagents. In this report, small ubiquitin-related modifier (SUMO) linked with a hexa-histidine tag was used as a fusion partner for the antitumor-analgesic peptide from the venom of Buthus martensii (Karsch) scorpion (AGAP). The optimal expression level of the soluble fusion protein, SUMO-AGAP, was up to 40% of the total cellular protein. The fusion protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Similar to other small peptides rich in disulfide bridges, high level expression of rAGAP in Escherichia coli is still a technical difficulty to produce a reduced cytosolic environment (Baneyx and Mujacic 2004). Although several approaches have been used to promote soluble expression of AGAP in Escherichia coli, and SUMO fusion technology has dramatically improved expression of soluble rAGAP, unsatisfactory yields and bioactivities remain a major bottleneck for further application (Cao et al 2010;Liu et al 2003). Promotion of disulfide bridge formation in Escherichia coli and in vitro oxidative renaturation are still good choices for production of high active AGAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other small peptides rich in disulfide bridges, high level expression of rAGAP in Escherichia coli is still a technical difficulty to produce a reduced cytosolic environment (Baneyx and Mujacic 2004). Although several approaches have been used to promote soluble expression of AGAP in Escherichia coli, and SUMO fusion technology has dramatically improved expression of soluble rAGAP, unsatisfactory yields and bioactivities remain a major bottleneck for further application (Cao et al 2010;Liu et al 2003). Promotion of disulfide bridge formation in Escherichia coli and in vitro oxidative renaturation are still good choices for production of high active AGAP.…”
Section: Introductionmentioning
confidence: 99%
“…Most scorpion analgesic peptides, but not BmK AGAP, are b-toxins (Ma et al 2010) and act on voltage-sensitive sodium channels. BmK AGAP exhibits analgesic activity and antitumor activity in vivo (Cao et al 2010;Liu et al 2003) and inhibits the proliferation and migration of many malignant tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these polypeptides have been shown to affect the activities and functions of ion channels, such as sodium and potassium channels [2,3]. Analgesic-antitumor peptide (AGAP), one of these polypeptides, has been purified from the venom of B. martensii Karsch, and several studies have shown that AGAP has analgesic and antitumor activities [4,5]. For example, AGAP markedly prolongs the survival of mice with engrafted Ehrlich ascites tumor cells and suppresses the growth of S-180 fibrosarcoma efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Various toxic polypeptides, usually called scorpion toxins, were considered to be the major bioactive ingredients of OAS. Recently, one of these polypeptides, analgesic-antitumor peptide (AGAP), has been purified and its analgesic and antitumor activities have also been demonstrated in pharmacological studies (4,5). Small ubiquitin-related modifier-AGAP (SUMO-AGAP) is a product of recombinant AGAP (rAGAP) linked with a hexa-histidine tag by Escherichia coli ( E. coli ).…”
Section: Introductionmentioning
confidence: 99%
“…Small ubiquitin-related modifier-AGAP (SUMO-AGAP) is a product of recombinant AGAP (rAGAP) linked with a hexa-histidine tag by Escherichia coli ( E. coli ). In this expression system, SUMO was capable of significantly enhancing the expression and efficiently improving the accurate folding of AGAP; thereby, rAGAP significantly inhibited the proliferation of lymphoma and glioma (5). Accordingly, rAGAP appears to be an ideal candidate drug for antitumor therapy.…”
Section: Introductionmentioning
confidence: 99%